2004
DOI: 10.1177/1362361304040637
|View full text |Cite
|
Sign up to set email alerts
|

Autistic Spectrum Disorder

Abstract: This study analyses the prevalence of ASD, comorbidity, educational provision and ability in autistic children in a single health district, born between 1983 and 1996. The number of recorded diagnoses doubled over a 4 year period. This appeared to be due to greater recognition of ASD in more able children, in children initially presenting with ADHD, and possibly in females. ADHD accounted for a substantial proportion of comorbidity. Age at diagnosis appeared to be related to school placement. Cognitive ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…On the other hand, neurobehavioral diseases are found mainly in young patients and include autism spectrum disorders (ASD), such as autism, attention deficit disorder, Asperger's syndrome and other disorders [24]. For the most part, the causes of these neurological diseases remain largely unknown but it is thought that multiple factors are involved in each disease [1,2].…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, neurobehavioral diseases are found mainly in young patients and include autism spectrum disorders (ASD), such as autism, attention deficit disorder, Asperger's syndrome and other disorders [24]. For the most part, the causes of these neurological diseases remain largely unknown but it is thought that multiple factors are involved in each disease [1,2].…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…In contrast, neurobehavioral diseases are related to fetal brain and early post-partum development but are less well characterized at the cellular level. Both of these disease types involve genetic and environmental factors [24,25], and they also have multiple chronic infections [1-3, 26, 27]. Even less well characterized at the cellular and genetic level are the psychiatric disorders, such as schizophrenia, paranoia, bipolar disorders, depression and obsessive-compulsive disorders, but these diseases are also associated with the presence of chronic infections [3].…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is suggested that chronic infections in the central nervous system (CNS) might be associated with progressive neurodegeneration and/or neurobehavioral abnormalities [1][2][3][4] . Prolonged CNS infections with neurotropic pathogens, along with other underlying conditions such as autoimmune responses, vascular diseases, head injury, cerebral edema, changes in neurotransmitter concentrations, nutritional deficiencies, heavy metal poisoning, and effects of environmental toxins, might play roles in the pathogenesis of neurodegenerative and/or neurobehavioral diseases [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%